City of Bandung's Paradiplomacy in Efforts to Fulfill Society's Needs During the COVID-19 Pandemic - Melkis, Juan Carlos; Alam, Gilang Nur; Dermawan, Windy (Ilomata International Journal of Social Science, 2025)
This study explores how the City of Bandung employed paradiplomacy, particularly through sister city cooperation with Suwon (South Korea) and Liuzhou (China), to respond to urgent healthcare shortages during the COVID-19 pandemic. Using qualitative documentary analysis of government archives, official communications, media coverage, and academic sources, the study shows how Bandung mobilized long-standing international networks to secure 30,000 donated masks, directly alleviating local scarcity at a critical moment. More than symbolic engagement, this cooperation demonstrated that institutionalized paradiplomacy can function as an operational mechanism for crisis response, complementing national strategies and strengthening multilevel governance. The findings highlight Bandung’s proactive international outreach as a practical contribution with tangible health benefits, while also underscoring the broader theoretical relevance of paradiplomacy as part of global governance frameworks. Ultimately, the case illustrates the value of sister city diplomacy not only for emergency relief but also as a replicable model for enhancing resilience and adaptive local governance in wider development contexts.